Emotional intelligence at work / Hasnizawati Hashim, Rozieana A. Halid @ Khalid and Sharifah Zannierah Syed Marzuki - Hashim, Hasnizawati; A. Halid @ Khalid, Rozieana; Syed Marzuki, Sharifah Zannierah (2006)
Emotional intelligence can be defined as knowing what feels good, what feels bad and how to get from bad to good feeling. It consists of qualities such as self-awareness, motivation, empathy and social skills. Emotional Intelligence (EI) has been used interchangeably with the word Emotional Quotient (EQ). Unlike Intelligence Quotient (IQ), which does not increase after adolescence, emotional intelligence or EQ can be improved throughout life (Singh 2003). People with high EQ are able to balance between emotion and reason, aware of their own feeling, empathic and compassionate towards others and also show high sign of self esteem. Thus, they are happier, healthier and more successful in their relationship. On the other hand, low EQ which is associated with feelings such as anger, frustration, depression, fear, guilt, stress and failure are likely to lead to general unhappiness. This paper discusses the level of EQ required by different level of professions. Professions that need interaction with other people, working in informal teams, empathizing and understanding others are the ones which require emotional intelligence. In developing emotional intelligence, one needs to acquire certain emotional skills. These skills can be categorised into three dimension; emotional competency, emotional maturity and emotional sensitivity. These skills need to be learned by individuals in order to be star performers and successful achievers in their professional life.